Psychoanalysis, healing and life medicalization on a contemporary scenario of treatment of mental disorders - Carrijo, Christiane [UNESP]; Domingues, Maria Beatriz Bueno (FapUNIFESP (SciELO), 2024)
The aim of this article is to analyze the relevance of Psychoanalytic questions in the treatment of mental disorders within the context of contemporary Psychiatry based on a discussion about the phenomenon of the medicalization of life. It is a brief exploratory study on the healing in Freudian thought, with content analysis of Freud’s manuscripts and analysis of the investigated field. In the treatment of mental illnesses today, society expects an innovative psychopharmacology, in which the symptom disappearing must be the main objective of this kind of intervention. Psychoanalysis, in turn, takes into account the latent sense of a symptom and the discourse of the subject about its suffering toward a psychoanalytic service and marks its difference from proposals in which the healing of mental disorders is restricted and excessive to the use of psychotropic drugs and pathologizing diagnoses.
Psicoanálisis, curación y medicalización de la vida en el escenario contemporáneo del tratamiento de trastornos mentales
Psychanalyse, guérison et médicalisation de la vie dans la mise en scène contemporaine du traitement des troubles mentaux
Keywords: healing; Life medicalization; mental disorders; psychoanalysis